Factors that influences employee retention at CCM Chemicals Sdn Bhd (Pasir Gudang works) / Nurul Atiqah Abd Rashid - Abd Rashid, Nurul Atiqah (Faculty of Business and Management, 2020)
Retaining an employee in the organization have been an important factor in the organization because the organization will face a huge lose when the employees tend to leave the organization as the employees are one of the assets for the company. However, the retention of employees had become the major problem the organization had to face today. The purpose of the research is to identify whether all the factors such as training and development programs, compensation plans, and work life balance factor were related in influence employee retention at CCM Chemicals Sdn Bhd (Pasir Gudang Works). The data that had been collected among 76 from 109 employees in all the department from this organization. The data collected are key in by using SPSS (Statistical Package for Social Science) to analyze all the data that had been gathered through the questionnaire. Several analyses have been done by using the SPSS such as frequency distribution, descriptive analysis, reliability analysis, correlation analysis and multiple regression analysis. Based on the data obtained, there are only two independent variables (training and development and compensation) are significance with employee retention at CCM Chemicals Sdn Bhd (Pasir Gudang Works). Meanwhile, one of independent variable is work life balance which is no significant relationship on employee retention. This indicates that the independent variable and dependent variable move in the same direction as one variable increase the other variables also.